2021
DOI: 10.1175/jas-d-19-0291.1
|View full text |Cite
|
Sign up to set email alerts
|

A Physically Based Stochastic Boundary Layer Perturbation Scheme. Part I: Formulation and Evaluation in a Convection-Permitting Model

Abstract: We present a simple, physically consistent stochastic boundary layer scheme implemented in the Met Office’s Unified Model. It is expressed as temporally correlated multiplicative Poisson noise with a distribution that depends on physical scales. The distribution can be highly skewed at convection-permitting scales (horizontal grid lengths around 1 km) when temporal correlation is far more important than spatial. The scheme is evaluated using small ensemble forecasts of two case studies of severe convective sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Forecasting of convective events has had a ''step change'' in ability since the advent of convection-permitting models (e.g., Lean et al 2008;Clark et al 2016). In turn, this has led to improvements in the prediction of floods with a rapid rate of rise, i.e., both surface water and flash flooding (e.g., Roberts et al 2009;Cuo et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forecasting of convective events has had a ''step change'' in ability since the advent of convection-permitting models (e.g., Lean et al 2008;Clark et al 2016). In turn, this has led to improvements in the prediction of floods with a rapid rate of rise, i.e., both surface water and flash flooding (e.g., Roberts et al 2009;Cuo et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, this has led to improvements in the prediction of floods with a rapid rate of rise, i.e., both surface water and flash flooding (e.g., Roberts et al 2009;Cuo et al 2011). However, quantitative forecasting of convective precipitation still remains a key challenge due to uncertainty in spatial structure (e.g., Roberts and Lean 2008;Dey et al 2014Dey et al , 2016aFlack et al 2018), timing (e.g., Lean et al 2008), storm structure (e.g., Stein et al 2015) and intensity (e.g., Mittermaier 2014): these issues are covered in more detail by Clark et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found indeed too large temperature spread in the sub cloud layer in some of our ensembles. Clark et al (2021) suggest that a height-dependent length-scale could be used in the scheme. We did some tests where we replaced the constant eddy length-scale of 1,000 m by the Bougeault-Lacarrère mixing length.…”
Section: Discussionmentioning
confidence: 99%
“…) 1∕2 , a scaling factor depending on time-and length-scales, and a scaling parameter 𝛼. This formulation has similarities with the stochastic perturbation scheme of Clark et al (2021), where, starting from a simplified boundary-layer model and the assumption that turbulent eddies can be considered as random events following a Poisson distribution, they mathematically derive a perturbation of the temperature tendency representing the fluctuations around the mean due to the random presence of eddies.…”
Section: Implementation Of Stochastic Turbulence In Aromementioning
confidence: 99%
See 1 more Smart Citation